Thrombolysis for wake-up stroke versus non-wake-up unwitnessed stroke: EOS individual patient data meta-analysis - Kamogawa, Naruhiko; Miwa, Kaori; Toyoda, Kazunori; Jensen, Märit; Inoue, Manabu; Yoshimura, Sohei; Fukuda-Doi, Mayumi; Kitazono, Takanari; Boutitie, Florent; Ma, Henry; Ringleb, Peter A.; Wu, Ona; et al. (Stroke, 2024)
BACKGROUND: Stroke with unknown time of onset can be categorized into 2 groups; wake-up stroke (WUS) and unwitnessed stroke with an onset time unavailable for reasons other than wake-up (non-wake-up unwitnessed stroke, non-WUS). We aimed to assess potential differences in the efficacy and safety of intravenous thrombolysis (IVT) between these subgroups. METHODS: Patients with an unknown-onset stroke were evaluated using individual patient-level data of 2 randomized controlled trials (WAKE-UP [Efficacy and Safety of MRI-Based Thrombolysis in Wake-Up Stroke], THAWS [Thrombolysis for Acute Wake-Up and Unclear-Onset Strokes With Alteplase at 0.6 mg/kg]) comparing IVT with placebo or standard treatment from the EOS (Evaluation of Unknown-Onset Stroke Thrombolysis trial) data set. A favorable outcome was prespecified as a modified Rankin Scale score of 0 to 1 at 90 days. Safety outcomes included symptomatic intracranial hemorrhage at 22 to 36 hours and 90-day mortality. The IVT effect was compared between the treatment groups in the WUS and non-WUS with multivariable logistic regression analysis. RESULTS: Six hundred thirty-four patients from 2 trials were analyzed; 542 had WUS (191 women, 272 receiving alteplase), and 92 had non-WUS (42 women, 43 receiving alteplase). Overall, no significant interaction was noted between the mode of onset and treatment effect (P value for interaction=0.796). In patients with WUS, the frequencies of favorable outcomes were 54.8% and 45.5% in the IVT and control groups, respectively (adjusted odds ratio, 1.47 [95% CI, 1.01-2.16]). Death occurred in 4.0% and 1.9%, respectively (P=0.162), and symptomatic intracranial hemorrhage in 1.8% and 0.3%, respectively (P=0.194). In patients with non-WUS, no significant difference was observed in favorable outcomes relative to the control (37.2% versus 29.2%; adjusted odds ratio, 1.76 [0.58-5.37]). One death and one symptomatic intracranial hemorrhage were reported in the IVT group, but none in the control. CONCLUSIONS: There was no difference in the effect of IVT between patients with WUS and non-WUS. IVT showed a significant benefit in patients with WUS, while there was insufficient statistical power to detect a substantial benefit in the non-WUS subgroup. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: CRD42020166903.
Ursprünglich veröffentlicht: 8. März 2024
Gesehen am 04.04.2024